La responsabilidad penal derivada de la actuación médica: valoración teórica - normativa de la institución - Jacho Cajas, Carmen Cecilia (2010)
Today the world is witnessing a notorious increase in criminal litigation in relation to medical action and the liability derived from it, fueling the most heated controversies regarding the creation of new criminal types and in which physicians since their performance , provide the configuring characteristics of the criminal notion. The doctor in his actions describes a series of behaviors that generate responsibility, since he is not impregnable before the laws, and much more when the interests at stake are the health, physical integrity and life of man in general.